Genetic diversity within and between sulfonylurea‐resistant and susceptible populations of Schoenoplectus juncoides in Japan. (23rd May 2013) - Imaizumi, T; Kataoka, Y; Ogata, S; Uchino, A; Neve, Paul
Summary To reveal the effects of herbicide selection on genetic diversity in the outcrossing weed species Schoenoplectus juncoides, six sulfonylurea‐resistant (SU‐R) and eight sulfonylurea‐susceptible (SU‐S) populations were analysed using 40 polymorphic inter‐simple sequence repeat loci. The plants were collected from three widely separated regions: the Tohoku, Kanto and Kyushu districts of Japan. Genetic diversity values (Nei's gene diversity, h) within each SU‐S population ranged from h = 0.125 to h = 0.235. The average genetic diversity within the SU‐S populations was HS = 0.161, and the total genetic diversity was HT = 0.271. Although the HS of the SU‐R populations (0.051) was lower than that of the SU‐S populations, the HT of the SU‐R populations (0.202) was comparable with that of the SU‐S populations. Most of the genetic variation was found within the region for both the SU‐S and SU‐R populations (88% of the genetic variation respectively). Two of the SU‐R populations showed relatively high genetic diversity (h = 0.117 and 0.161), which were comparable with those of the SU‐S populations. In contrast, the genetic diversity within four SU‐R populations was much lower (from h = 0 to 0.018) than in the SU‐S populations. The results suggest that selection by sulfonylurea herbicides has decreased genetic diversity within some SU‐R populations of S. juncoides. The different level of genetic diversity in the SU‐R populations is most likely due to different levels of inbreeding in the populations.